Vertical handoffs in fourth-generation multinetwork environments. - McNair, J. (IEEE Wireless communications)
Revolutionary drivers for 4G include a push toward universal wireless access and ubiquitous computing through seamless personal and terminal mobility. One of the major challenges for seamless mobility is the criterion of a vertical handoff protocol: a handoff protocol for users that move between different types of networks. Traditional operations for handoff detection policies, decision metrics, and radio link transfer are not able to adapt to dynamic handoff criteria or react to user inputs and changing network availabilities. Nor are they able to deliver context-aware services or ensure network interoperability. Thus, new techniques are needed to manage user mobility between different types of networks. This article presents a tutorial on the design and performance issues for vertical hand-off in an envisioned multinetwork fourth-generation environment. Various network architectures and technologies for 3G and beyond are described, including wireless LANs, cellular, satellite, and Mobile IP. Then the problem of vertical handoff is defined in the context of such a diverse network environment. Finally, research efforts to resolve the open problems are explored, including new techniques for dynamic handoff decision and detection algorithms and context-aware radio link transfer.